Acute kidney injury in cats and dogs: A proportional meta-analysis of case series studies - Legatti, Sabrina Almeida Moreira [UNESP]; Dib, Regina El [UNESP]; Legatti, Emerson [UNESP]; Botan, Andresa Graciutti [UNESP]; Camargo, Samira Esteves Afonso [UNESP]; Agarwal, Arnav; Barretti, Pasqual [UNESP]; Paes, Antônio Carlos [UNESP] (Public Library of Science (PLoS), 2018)
Introduction Risk of mortality in the setting of acute kidney injury (AKI) in cats and dogs remains unclear. Objectives To evaluate the incidence of mortality in cats and dogs with AKI based on etiology (i.e. infectious versus non-infectious; receiving dialysis versus conservative treatment). Materials and methods Ovid Medline, EMBASE, and LILACS were searched up to July 2016. Articles were deemed eligible if they were case series studies evaluating the incidence of all-cause mortality in cats and dogs with AKI, regardless of etiology or the nature of treatment. Results Eighteen case series involving 1,201animalsproved eligible. The pooled proportions for overall mortality were: cats53.1% [95% CI 0.475, 0.586; I2 = 11,9%, p = 0.3352]; dogs 45.0% [95% CI 0.33, 0.58; I2 = 91.5%, P < 0.0001]. A non-significant increase in overall mortality risk was found among dialysed animals relative to those managed with conservative treatment, independent of animal type and the etiology of their AKI. The pooled proportions for overall mortality according to etiology, regardless of treatment type, were: AKI due infectious etiology for cats and dogs, 19.2% [95% CI 0.134, 0.258; I2 = 37.7%, P = 0.0982]; AKI due non-infectious etiology for cats and dogs, 59.9% [95% CI 0.532, 0.663; I2 = 51.0%, P = 0.0211]. Conclusion Our findings suggest higher rates of overall mortality in cats and dogs with AKI due to noninfectious etiologies relative to infectious etiologies, and showed non-significant differences in terms of higher rates associated with dialysis compared to conservative management. Further investigations regarding optimal time to initiate dialysis and the development of clinical models to prognosticate the course of disease and guide optimal treatment initiation for less severe cases of AKI in cats and dogs is warranted.